Indefinite: doing time in jail - Walker, Michael L. (Oxford scholarship online, 2022)
'Indefinite' is an ethnographic study of life in a contemporary county jail system. Having been arrested and jailed, Michael L. Walker turned his experience into an examination of jails from the inside out, revealing the physical and emotional experience of doing time, the set of strategies prisoners use to endure it, and the deputies who use race to control prisoners and the kinds of experiences prisoners had.